Moral Values in ‘Peter Pan’ Short Story Book - Marpaung, Tiara Azzahra; Maisarah, Ira (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The aim of the present study is to analyze the moral values that represented in the short story book entitled 'Peter Pan' written by Arianna Candell and published by Eaststar Adhi Citra. This study used descriptive qualitative method. This study found that from 18 moral values, there are 10 values that contained in the short story with the majority of occurrences found are one or two times. The value that found are love of peace, appreciate achievements, responsibility, friendly, tolerance, creative, like reading, curiosity, social care and hard work. This study contributes to building student character education by understanding the meaning of moral values contained in learning media. For future study, it is suggested to examine more complex literary works such as novels and use a different theory than the present study.